Análisis de los factores determinantes en la educación financiera de estudiantes universitarios: evidencia de la Universidad Tecnológica de Bolívar en el caribe colombiano (2025)
Financial intelligence has become an essential skill for personal and professional development, particularly among university students who are required to make critical financial decisions early in life. This study analyzes the factors that determine the level of financial intelligence among undergraduate students at the Universidad Tecnológica de Bolívar, focusing on the influence of family education, academic training, interest in financial topics, and emotional intelligence. Using Probit and multinomial Logit econometric models applied to a representative sample of 357 students, the research identifies significant relationships between these variables and financial literacy levels. The results show that higher university-level financial education, greater emotional intelligence, higher financial independence, and a proactive attitude toward financial learning are positively associated with higher financial intelligence. These findings highlight the need to implement more comprehensive educational strategies to strengthen financial literacy within university contexts, particularly in regions such as the Colombian Caribbean, where structural challenges related to poverty and inequality persist. This study provides valuable insights for the design of public policies and academic programs aimed at improving young people's financial well